On the inertia of power electronics converters - Castro, André Ramos de (2018)
Electrical power systems are going through a transition in its energy matrix. Renewable energy sources based generation and distributed generation grow in number. There is a concern among academics and system operators that the lack of spinning mass’ inertia in these new generating units will negatively contribute to frequency stability in electrical power systems. However, there is not an adequate established method for quantifying the contribution a power electronics based generating unit provides to grid frequency stability. This work seeks to define such a method and to analyze control techniques from the point of view of contribution to electrical power systems frequency stability.